Comparing the Use of 3D Photogrammetry and Computed Tomography in Assessing the Severity of Single-Suture Nonsyndromic Craniosynostosis. Issue 2 (May 2017) - Ho, Olivia A.; Saber, Nikoo; Stephens, Derek; Clausen, April; Drake, James; Forrest, Christopher; Phillips, John
Purpose: Single-suture nonsyndromic craniosynostosis is diagnosed using clinical assessment and computed tomography (CT). With increasing awareness of the associated risks of radiation exposure, the use of CT is particularly concerning in patients with craniosynostosis since they are exposed at a younger age and more frequently than the average child. Three-dimensional (3D) photogrammetry is advantageous—it involves no radiation, is conveniently obtainable within clinic, and does not require general anaesthesia. This study aims to assess how 3D photogrammetry compares to CT in the assessment of craniosynostosis severity, to quantify surgical outcomes, and analyze the validity of 3D photogrammetry in craniosynostosis. Methods: Computed tomography images and 3D photographs of patients who underwent craniosynostosis surgery were assessed and aligned to best fit. The intervening area between the CT and 3D photogrammetry curves at the supraorbital bar (bandeau) level in axial view was calculated. Statistical analysis was performed using Student t test. Ninety-five percent confidence intervals were determined and equivalence margins were applied. Results: In total, 41 pairs of CTs and 3D photographs were analyzed. The 95% confidence interval was 198.16 to 264.18 mm 2 and the mean was 231.17 mm 2 . When comparisons were made in the same bandeau region omitting the temporalis muscle, the 95% confidence interval was 108.94 to 147.38 mm 2, and the mean was 128.16 mm 2 . Although statistically significant difference between the modalities was found, they can be attributable to the dampening effect of soft tissue. Conclusion: Within certain error margins, 3D photogrammetry is comparable to CT in assessing the severity of single-suture nonsyndromic craniosynostosis. However, a dampening effect can be attributable to the soft tissue. Three-dimensional photogrammetry may be more applicable for severe cases of craniosynostosis but not milder deformity. It may also be beneficial for assessing the overall appearance and aesthetics but not for determining underlying bony severity.